Knowledge-building in adaptation management: concertación processes in transforming Lima water and climate change governance. (October 2014) - Miranda Sara, Liliana; Baud, Isa
Recently, three processes were used to analyze the consequences of plausible climate change scenarios for urban water governance in Lima. The first process, led by a German-financed research team, developed climate change scenarios using innovative tools. The second, Chance2Sustain, brought spatial perspectives to urban development and water governance, mapping spatial inequities in water-related vulnerabilities and including community-based knowledge. The Metropolitan Municipality of Lima (MML) initiated the third process, to prepare a city development and Climate Change Adaptation Strategy. This paper examines how these processes of knowledge construction contributed to transitions in water governance and climate change adaptation strategies. Although all processes used concertación (1) in their knowledge construction, the actors and the incorporated knowledge differed considerably. While the first example was dominated by professional groups and technical–professional knowledge, the Chance2Sustain and city processes included a wider range of actors and shifted thinking about adaptive management towards including contextual-embedded knowledge.